Effect of Dietary Modification on Gastric Mucosa, Gastrointestinal Symptoms and Nutritional Status of Patients With Early Gastric Cancer After Endoscopic Submucosal Dissection Surgery: A Retrospective Cohort Study - Zhang, Yebing; Liu, Chengxia; Ma, Xingbin; Xu, Lei; Wang, Xiuhua; Wang, Xin; Cao, Jingrun; Ma, Aiguo; Gao, Tao (Frontiers in Nutrition, 2022)
Food is an important factor affecting the treatment of patients with early gastric cancer (EGC). We have established a hospital cohort to guide dietary patterns and observe the health status of patients with EGC after endoscopic submucosal dissection (ESD) after dietary modification. A total of 273 patients with EGC who underwent ESD were recruited to the cohort. They were given dietary instruction and education through a dietary manual and were followed up for 12 months. If the dietary pattern changed to the “traditional food” pattern (high consumption of vegetables, wheat products, and red meat) after the nutritional guidance, subjects were defined as the improvement diet group. Dietary patterns focused on “alcohol and fish” (drink a lot of wine and beer and eating freshwater and marine fish) or “coarse cereals” (mainly whole grains, beans and poultry) were the main ones in the unimproved diet group. The nutritional status, gastric mucosa, and gastrointestinal symptoms of the two groups of patients before and after the dietary instruction were compared. Compared with the unimproved diet group, the endoscopic performance score and the symptom score in the improved diet group were decreased by an average of 1.31 and 1.90, respectively. Except for lymphocyte count (P = 0.227), total protein (P < 0.000), albumin (P = 0.003), globulin (P = 0.014), red blood cell count (P < 0.000), and hemoglobin (P < 0.000) values were improved to varying degrees. After changing the diet, the intake of wheat products and vegetables in the improved diet group increased by 15.58 and 17.52%, respectively, while the intake of alcohol, fish, and pickled products was reduced by 43.36, 36.43, and 31.41%, respectively. After 1 year of dietary adjustment, the nutritional status, gastric mucosa, and gastrointestinal symptoms of patients with EGC after ESD eating the "traditional food" diet were all improved.